1999
DOI: 10.1074/jbc.274.30.21056
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inhibitor of Matrix Metalloproteinase-2 Regulates Matrix Metalloproteinase-2 Activation by Modulation of Membrane-type 1 Matrix Metalloproteinase Activity in High and Low Invasive Melanoma Cell Lines

Abstract: Activation of pro-matrix metalloproteinase (MMP)-2 on the surface of malignant cells by membrane-bound MT1-MMP is believed to play a critical role during tumor progression and metastasis. In this study we present evidence that MT1-MMP plays a key role for the in vitro invasiveness of malignant melanoma. Melanoma cell lines secreted latent MMP-2 when cultured on plastic. However, when cells were grown in floating type I collagen lattices, only high invasive melanoma cells activated proMMP-2. Activation could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
115
1
2

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 44 publications
17
115
1
2
Order By: Relevance
“…Indeed, we showed that Dec-RVKR-CH 2 Cl reduced proMMP-2 activation in stimulated cartilage. This is consistent with the results of several previous studies, which have shown that the addition of Dec-RVKR-CH 2 Cl to cell cultures prevents proMMP-2 activation by blocking furin-dependent activation of proMT-MMPs (39,(57)(58)(59)(60).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we showed that Dec-RVKR-CH 2 Cl reduced proMMP-2 activation in stimulated cartilage. This is consistent with the results of several previous studies, which have shown that the addition of Dec-RVKR-CH 2 Cl to cell cultures prevents proMMP-2 activation by blocking furin-dependent activation of proMT-MMPs (39,(57)(58)(59)(60).…”
Section: Discussionsupporting
confidence: 93%
“…40 Induction of the activated form of MMP-2 was associated with enhanced expression of MT1-MMP, which activates MMP-2. 25,27,28 These results suggest that basigin stimulates activation as …”
Section: Basigin-dependent Induction Of Mmps and Mmp-2 Activity In Comentioning
confidence: 78%
“…20 MT1-MMP triggers tumor invasion by activating MMP-2. 25,27,28 Cutaneous MM is characterized by a high potential for invasion and metastasis. Previous studies reported the involvement of MMPs in migration, invasion, metastasis and progression of MM.…”
mentioning
confidence: 99%
“…Based on our findings that COS-1 cells can process wild-type MT1-MMP as well as its 108 RRKR mutant, coupled with the recent demonstration that ā£ 1 PI PITT is unable to efficiently inhibit proprotein convertase-dependent pathways (Vollenweider et al, 1996;Cui et al, 1998), we propose that the removal of the MT1-MMP prodomain is a prerequisite for the efficient display of proteolytic activity. Interestingly, although partial blockade of proMT1-MMP processing was reported recently with a chloromethylketone inhibitor (Maquoi et al, 1998;Kurschat et al, 1999), this agent is not specific for proprotein convertases and also exerts cytotoxic effects (Hallenberger et al, 1992;Okumura et al, 1997;Jean et al, 1998).…”
Section: Proprotein Convertases As Processing Enzymes For Mt1-mmpmentioning
confidence: 99%